2013
DOI: 10.1007/s00449-013-0894-6
|View full text |Cite
|
Sign up to set email alerts
|

Sonication-assisted production of biodiesel using soybean oil and supercritical methanol

Abstract: High temperature and pressure are generally required to produce biodiesel using supercritical methanol. We reduced the harsh reaction conditions by means of sonicating the reaction mixture prior to transesterification using supercritical methanol. Soybean oil was selected as the raw material for transesterification. As soybean oil contains more unsaturated fatty acid triglycerides, the biodiesel degraded more at high temperature. The reactants were sonicated for 60 min at 35 °C prior to transesterification to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The GCMS analysis obtained 18 compounds that predominated in the three soybean varieties including saturated and unsaturated fatty acids, most of which contain ingredients such as n-Hexadecanoic acid, Hexadecanoic acid, ethyl ester (CAS), (E.)-9-Octadecenoic acid ethyl ester, Hexadecane, Cis-9-Hexadecenal, Octadecena, 9-Octadecenoic acid (Z)-(CAS)/olead acid [53,54]. For Cis-9-Hexadecenal fatty acids, the Dega-1 has an area of 17.12% and 11.61% for Gepak Kuning while the Grobongan does not detect these fatty acid compounds, but almost all fats must have Cis-9-Hexadecenal fatty acid compounds [54][55][56]. Cis-9-Hexadecenal is classified as an antifungal activity that has the potential for anti-melanogenic antifungal properties [57].…”
Section: Soybean Seeds Compound Componentsmentioning
confidence: 99%
“…The GCMS analysis obtained 18 compounds that predominated in the three soybean varieties including saturated and unsaturated fatty acids, most of which contain ingredients such as n-Hexadecanoic acid, Hexadecanoic acid, ethyl ester (CAS), (E.)-9-Octadecenoic acid ethyl ester, Hexadecane, Cis-9-Hexadecenal, Octadecena, 9-Octadecenoic acid (Z)-(CAS)/olead acid [53,54]. For Cis-9-Hexadecenal fatty acids, the Dega-1 has an area of 17.12% and 11.61% for Gepak Kuning while the Grobongan does not detect these fatty acid compounds, but almost all fats must have Cis-9-Hexadecenal fatty acid compounds [54][55][56]. Cis-9-Hexadecenal is classified as an antifungal activity that has the potential for anti-melanogenic antifungal properties [57].…”
Section: Soybean Seeds Compound Componentsmentioning
confidence: 99%
“…Some of the technologies have been applied successfully in commercial production (Qiu et al, 2010) where the reaction rate is greatly enhanced and thus residence time may be reduced. To reduce the limitations of mass and heat transfer in chemical reactions, literature recommends to conduct such reactions in micro-reactors (Pohar and Plazl, 2008;Hessel et al, 2005;Wen et al, 2009) and in packed bed reactors (Yu et al, 2010;Santacesaria et al, 2011;Su, 2011) or assisted reaction with hydrodynamic cavitation (Gogate et al, 2008;Sedahmed et al, 2011;, microwave (Gole and Gogate, 2013) and ultrasound Gole and Gogate, 2013;Gobikrishnan et al, 2013).…”
Section: Intensification Technologies In Continuous Mode For Scmmentioning
confidence: 99%
“…Recently, the work of Gobikrishnan et al (2013) showed that the severity of the supercritical reactions was reduced by including sonication prior to the reaction. The authors reported that the mixture was sonicated at high intensity and a frequency of 40 kHz for 60 min at 308 K prior to transesterification by supercritical methanol in batch-mode to reduce the mass-transfer resistance between the oil and alcohol phases and the hence minimize harsh reaction conditions.…”
Section: Intensification Technologies In Continuous Mode For Scmmentioning
confidence: 99%
“…Among the alternatives found to solve this problem, we highlight the research related to biofuels, taking as an example, biodiesel [3]. This fuel has advantages when compared to petrodiesel, as derived from renewable sources, biodegradable, non-toxic, possessing significant lubricity and practically free of sulfur and aromatics [4].…”
Section: Introductionmentioning
confidence: 99%